Students' preferences towards correction of classroom oral errors - a case study in Can Tho univesity : - Phạm, Thị Mận (Can Tho University, 2008)
Making errors is unavoidable in learning and using English, especially in the environment of EFL in Viet Nam. Those errors have significant roles with teachers, and learners. Error correction to help learners speak English more accurately is important.